Developing Learning Material Model for English for Specific Purpose (ESP) in Accounting Department of Riau University - Erna Nawir; Alber Alber; Widya Syafitri (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2021)
The confusion of lecturers in teaching English with specific and suitable material for students who choose majors other than the English department is the main problem mostly encountered found by the writers is the basic reason for conducting this research. The main purpose of having this article is to fill the absence of material provided for students in Accounting Department in Riau University. Through descriptive methods, qualitative approaches and instruments used in the form of a close-ended questionnaire in which the form of questions refer to the need analysis proposed by Hutchinson & Water (necessities, wants, and lacks) of the students, initialized and complemented with their latest English language level and an adaptation questionnaire from Adnan was researched as well. The data was obtained from a number of students majoring in Accounting for academic year of 2020/2021 class E at the Faculty of Economics, Riau University which were converted to frequency and rounded to a percentage. Dominated by students who have basic English skills, the students have various necessities, wants, and lacks in learning English. Eventually based on the finding, a proposed material model was framed.